European guidelines from the EHTG and ESCP for Lynch syndrome: an updated third edition of the Mallorca guidelines based on gene and gender. Issue 5 (26th May 2021) - Seppälä, T T; Latchford, A; Negoi, I; Sampaio Soares, A; Jimenez‐Rodriguez, R; Sánchez‐Guillén, L; Evans, D G; Ryan, N; Crosbie, E J; Dominguez‐Valentin, M; Burn, J; Kloor, M; et al.
Abstract: Background: Lynch syndrome is the most common genetic predisposition for hereditary cancer but remains underdiagnosed. Large prospective observational studies have recently increased understanding of the effectiveness of colonoscopic surveillance and the heterogeneity of cancer risk between genotypes. The need for gene‐ and gender‐specific guidelines has been acknowledged. Methods: The European Hereditary Tumour Group (EHTG) and European Society of Coloproctology (ESCP) developed a multidisciplinary working group consisting of surgeons, clinical and molecular geneticists, pathologists, epidemiologists, gastroenterologists, and patient representation to conduct a graded evidence review. The previous Mallorca guideline format was used to revise the clinical guidance. Consensus for the guidance statements was acquired by three Delphi voting rounds. Results: Recommendations for clinical and molecular identification of Lynch syndrome, surgical and endoscopic management of Lynch syndrome‐associated colorectal cancer, and preventive measures for cancer were produced. The emphasis was on surgical and gastroenterological aspects of the cancer spectrum. Manchester consensus guidelines for gynaecological management were endorsed. Executive and layperson summaries were provided. Conclusion: The recommendations from the EHTG and ESCP for identification of patients with Lynch syndrome, colorectal surveillance, surgical management of colorectal cancer, lifestyle and chemoprevention in Lynch syndrome that reached a consensus (at least 80 per cent) are presented.